Differentiating neurodegenerative parkinsonian syndromes using vestibular evoked myogenic potentials and balance assessment. Issue 11 (November 2021) - Klunk, Dietrich; Woost, Timo B.; Fricke, Christopher; Classen, Joseph; Weise, David
Highlights: Ocular Vestibular Evoked Myogenic Potentials (oVEMP) and posturography may help to distinguish between different entities of parkinsonism. Cervical VEMP are not significantly altered in patients with parkinsonian syndromes. No correlation was found between VEMP and posturographic parameters. Abstract: Objective: Vestibular evoked myogenic potentials (VEMP) were investigated to differentiate between parkinsonian syndromes. We correlated balance and VEMP parameters to investigate the VEMP brainstem circuits as possible origin for postural instability. Methods: We assessed clinical status, ocular and cervical VEMP (oVEMP, cVEMP) and conducted a balance assessment (posturography, Activities-specific Balance Confidence Scale, Berg Balance Scale, modified Barthel Index) in 76 subjects: 30 with Parkinson's disease (PD), 16 with atypical parkinsonism (AP) and 30 healthy controls. VEMP were elicited by using a mini-shaker on the forehead. Results: Patients with PD had a prolonged oVEMP n10 in comparison to controls and prolonged p15 compared to controls and AP. Patients with AP showed reduced oVEMP amplitudes compared to PD and controls. CVEMP did not differ between groups. Postural impairment was higher in AP compared to controls and PD, particularly in the rating scales. No correlations between VEMP and posturography were found. A support vector machine classifier was able to automatically classify controls and patient subgroups with moderate to good accuracy based on oVEMP latencies and balance questionnaires. Conclusions: Both oVEMP and posturography, but not cVEMP, may be differentially affected in PD and AP. We did not find evidence that impairment of the cVEMP or oVEMP pathways is directly related to postural impairment. Significance: OVEMP and balance assessment could be implemented in the differential diagnostic work-up of parkinsonian syndromes.